Wavefront-Guided Laser in Situ Keratomileusis (Lasik) versus Wavefront-Guided Photorefractive Keratectomy (Prk): A Prospective Randomized Eye-to-Eye Comparison (An American Ophthalmological Society Thesis) - Manche, Edward E. (The American Ophthalmological Society, 2011)
PURPOSE: To compare the safety and efficacy of wavefront-guided laser in situ keratomileusis (LASIK) vs photorefractive keratectomy (PRK) in a prospective randomized clinical trial. METHODS: A cohort of 68 eyes of 34 patients with −0.75 to −8.13 diopters (D) of myopia (spherical equivalent) were randomized to receive either wavefront-guided PRK or LASIK in the fellow eye using the VISX CustomVue laser. Patients were evaluated at 1 day, 1 week, and months 1, 3, 6, and 12. RESULTS: At 1 month, uncorrected visual acuity (UCVA), best spectacle-corrected visual acuity (BSCVA), 5% and 25% contrast sensitivity, induction of higher-order aberrations (HOAs), and subjective symptoms of vision clarity, vision fluctuation, ghosting, and overall self-assessment of vision were worse (P<0.05) in the PRK group. By 3 months, these differences had resolved (P>0.05). At 1 year, mean spherical equivalent was reduced 94% to −0.27 ± 0.31 D in the LASIK group and reduced 96% to −0.17 ± 0.41 D in the PRK group. At 1 year, 91% of eyes were within ±0.50 D and 97 % were within ±1.0 D in the PRK group. At 1 year, 88% of eyes were within ±0.50 D and 97% were within ±1.0 D in the LASIK group. At 1 year, 97% of eyes in the PRK group and 94% of eyes in the LASIK group achieved an UCVA of 20/20 or better (P=0.72). Refractive stability was achieved in both PRK and LASIK groups after 1 month. There were no intraoperative or postoperative flap complications in the LASIK group. There were no instances of corneal haze in the PRK group. CONCLUSIONS: Wavefront-guided LASIK and PRK are safe and effective at reducing myopia. At 1 month postoperatively, LASIK demonstrates an advantage over PRK in UCVA, BSCVA, low-contrast acuity, induction of total HOAs, and several subjective symptoms. At postoperative month 3, these differences between PRK and LASIK results had resolved.